2023
DOI: 10.1038/s41598-023-27829-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis of postoperative delirium in nonagenarians with hip fracture

Abstract: Hip fractures in nonagenarians is one of the great challenges for patients of this age, the family and the larger society. The purpose of this study was to investigate the risk factors and prognosis of postoperative delirium in nonagenarians with hip fracture. 199 Eligible patients were enrolled. Confusion Assessment Method (CAM) were used to identify the delirium. Logistic regressions were used to investigate the effect of 18 pre-existing conditions on postoperative delirium. Prognosis of postoperative deliri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, Lu et al reported that SIRI was positively correlated with the occurrence of postoperative delirium in older patients with hip arthroplasty surgery ( 44 ). Numerous studies have confirmed that postoperative delirium in hip fracture patients was obviously associated with poor outcomes, including higher mortality ( 45 , 46 ). Thus, the positive association between SIRI and mortality may be partially explained by its association with complications after hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lu et al reported that SIRI was positively correlated with the occurrence of postoperative delirium in older patients with hip arthroplasty surgery ( 44 ). Numerous studies have confirmed that postoperative delirium in hip fracture patients was obviously associated with poor outcomes, including higher mortality ( 45 , 46 ). Thus, the positive association between SIRI and mortality may be partially explained by its association with complications after hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In this particular investigation, the mECM was employed to detect comorbidities in patients upon admission utilizing 30 unique medical conditions and screened and further stratified into groups 1–5 representing <0, 0, 1–5, 6–13, ≥14, respectively. Prior research has illustrated that this technique is significantly more effective at accounting for comorbidities than other approaches, resulting in a more accurate forecast of complications and mortality 15 , 16 . Functional independence measures (FIM) was utilized to assess and determine the patients’ capability to carry out their everyday tasks and perform their activities of daily living.…”
Section: Methodsmentioning
confidence: 99%
“…1 Previous study reported that the incidence of delirium after surgery ranges from 20% to 45% among older patients. 2 POD is linked to with neuropsychiatric symptoms, longer hospital stay, higher medical expenditures and lower in activities of daily living, [3][4][5] especially in older patients. More importantly, POD can also potentially be associated with the long-term cognitive dysfunction, dementia and even an increase in mortality.…”
Section: Introductionmentioning
confidence: 99%